2022
DOI: 10.47982/jfde.2022.powerskin.5
|View full text |Cite
|
Sign up to set email alerts
|

Timber-based Façades with Different Connections and Claddings: Assessing Materials’ Reusability, Water Use and Global Warming Potential

Abstract: Timber-based façade technologies have the potential to effectively reduce the carbon footprint, reduce water use in construction, and minimize waste, when their manufacturing process is highly prefabricated. Additionally, avoiding glue parts can enhance the sustainability of the façade as its elements can be replaced (extending the durability of façades and therefore buildings) and separated once that they reach their end of life (to re-use or recycle them). Thus, the connection between materials might have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…This study revealed that, compared to the baseline, an increase in disassembly potential of up to 100% can be achieved for an end-of-life scenario reusing the building envelope element at large and an increase of up to 49% on the level of materials and components being applied. In line with previous research (Juaristi et al, 2022), this research, therefore, advocates that, based on a careful design process and within the framework of existing product certification, it is possible to substantially increase future reuse potential contributing to improved material efficiency in the construction sector.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…This study revealed that, compared to the baseline, an increase in disassembly potential of up to 100% can be achieved for an end-of-life scenario reusing the building envelope element at large and an increase of up to 49% on the level of materials and components being applied. In line with previous research (Juaristi et al, 2022), this research, therefore, advocates that, based on a careful design process and within the framework of existing product certification, it is possible to substantially increase future reuse potential contributing to improved material efficiency in the construction sector.…”
Section: Discussionsupporting
confidence: 70%
“…However, beyond efficiency gains, the full potential of prefab façade elements has not yet been met, and substantial improvements can be achieved to improve the level of sustainability, circularity, and customization in a way that does not increase project risks, complexity, and building costs of renovation projects (Juaristi et al, 2022;Lam et al, 2022). The level of circularity of prefab façade elements can be substantially improved by facilitating access to individual components of the product system, thereby facilitating refurbishing, reuse, and recycling (Chung et al, 2014;Kimura et al, 2001;Ma & Kremer, 2016;Okudan Kremer et al, 2013).…”
Section: Prefabricated Circular Building Envelope Elements For Carbon...mentioning
confidence: 99%
See 3 more Smart Citations